2019
DOI: 10.1093/aesa/saz032
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Phenotypic Plasticity in the South American Locust, Schistocerca cancellata (Orthoptera: Acrididae)

Abstract: Historically, the South American locust, Schistocerca cancellata (Serville, 1838), has been considered the most serious agricultural pest in Argentina. An outbreak of a magnitude not recorded since 1954 started in 2015 through 2017 in northern Argentina and neighboring Paraguay and Bolivia. Schistocerca cancellata is widely considered as a true locust, with pronounced locust phase polyphenism, although the expression of its phenotypic plasticity has never been quantitatively tested under different density cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
0
23
0
4
Order By: Relevance
“…Among locust species, solitarious nymphs are often cryptically coloured and green, while gregarious nymphs exhibit black patterns on a yellow, orange, or red background colouration 15 , 16 , 29 , 38 , 40 , 51 – 53 . In addition, solitarious and gregarious locusts exhibit species-specific differences in their size 20 , 28 , 51 , and the ratio of the hind femur length over the head width (F/C ratio) is considered a reliable predictor of the phase state, with larger values observed in solitarious individuals 20 , 40 , 51 , 54 . Thus, we hypothesised that the four species would exhibit varying levels of plastic reaction norms in these traits, and that there would be a similar spectrum of reaction norms in morphology among the species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among locust species, solitarious nymphs are often cryptically coloured and green, while gregarious nymphs exhibit black patterns on a yellow, orange, or red background colouration 15 , 16 , 29 , 38 , 40 , 51 – 53 . In addition, solitarious and gregarious locusts exhibit species-specific differences in their size 20 , 28 , 51 , and the ratio of the hind femur length over the head width (F/C ratio) is considered a reliable predictor of the phase state, with larger values observed in solitarious individuals 20 , 40 , 51 , 54 . Thus, we hypothesised that the four species would exhibit varying levels of plastic reaction norms in these traits, and that there would be a similar spectrum of reaction norms in morphology among the species.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the well-resolved phylogeny of the genus 26 , 27 , we now know that the desert locust ( S. gregaria ), for which we have extensive data on the proximate mechanisms of locust phase polyphenism 19 , occupies the basal position and is sister to the rest of the genus, which implies that the ancestral condition for the genus is the presence of density-dependent phenotypic plasticity 26 . Importantly, the three locust species in the genus, the desert locust, the Central American locust ( S. piceifrons (Walker)), and the South American locust ( S. cancellata (Serville)), do not form a monophyletic group, which suggests that locust phase polyphenism has been lost and gained multiple times 26 , 28 , 29 . Furthermore, recent studies have shown that non-swarming sedentary grasshopper species in the genus have the ability to exhibit varying degrees of density-dependent phenotypic plasticity in behaviour, colour, and morphology 26 , 30 33 , suggesting that some aspects of density-dependent phenotypic plasticity may be phylogenetically conserved 26 , 29 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory, the nymphal body size is affected by rearing density, and there is a sex-dependent pattern. Crowded final instar female nymphs are smaller than those reared isolated, while crowded male nymphs are larger, resulting in a less pronounced body size difference between crowded males and females [9] (Table 1). In the field, sexual dimorphism has not been thoroughly studied, though recent observations in Argentina (Piou et al, unpublished data) suggest that female nymphs are larger than males.…”
Section: Biology and Ecology Of S Cancellatamentioning
confidence: 99%
“…Schitoscerca cancellata tiene metamorfosis gradual, completa su ciclo a través de los estados de huevo, ninfa (juveniles) y adulto, y se caracteriza porque tiene dos fases, solitaria y gregaria. Pocco et al (2019) establecieron que las hembras y los machos desarrollados de manera solitaria tienen un largo de cuerpo de 66.0 mm (60.0-70.8) y 52.7 mm (47.5-56.1), respectivamente. Cuando se desarrollan en densidades poblacionales muy altas las hembras miden 67.2 mm (52.3-75.3) y los machos 58.1 (47.5-65.4).…”
Section: Biología Y Ecologíaunclassified
“…Tienden a agruparse en "bandas" y trasladarse a través de la vegetación, caminos y rutas (De Wysiecki & Lange, 2005). En la fase solitaria, cuando los individuos están en bajas densidades, las ninfas son de color verde (Pocco et al, 2019).…”
Section: Biología Y Ecologíaunclassified